Membangun Desa Kertamukti Melalui Edukasi Keamanan Cyber dalam Partisipasi Masyarakat - Rasim (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Kertamukti Village faces challenges in increasing public awareness and participation in digital security in the technological era. This study aims to build public awareness through cybersecurity education, citizen data management, and implementation of CCTV-based security technology. Education is provided in the form of training that includes an introduction to cyber threats, how to protect personal data, and good online security practices. In addition, citizen data is inputted digitally with a secure system to support efficient village administration management. As a mitigation measure, CCTV installation in strategic areas of the village is also carried out to improve physical and digital security. The results of this program show an increase in public understanding of the importance of cybersecurity, efficiency in managing citizen data, and strengthening village environmental security. This initiative is expected to be a sustainable model to be implemented in other villages in order to support safe and inclusive digital transformation